Biology and control of bean anthracnose in Ethiopia - Beshir Mohamed, Tesfaye (University of the Free State, 2003)
Common bean (Phaseolus vulgaris L.) is an important food legume for millions of Ethiopian people. However, diseases are major constraints in bean production with anthracnose, caused by Colletotrichum lindemuthianum (Sacc. & Magn.) Briosi and Cav. (teleomorph = Glomerella cingulata (Stonem.), being of particular concern. Anthracnose is the most important disease of bean in Ethiopia and can cause complete yield losses on susceptible cultivars when contaminated seed are planted. The impact of epidemics is further enhanced when favourable environmental conditions prevail. The main objective of this study was to provide information that can be used as part of an integrated control program for anthracnose in Ethiopia. Field surveys were conducted in the foremost bean growing areas of Ethiopia to acquire information on the geographical distribution of anthracnose. Similar to bean rust, anthracnose is favoured by high moisture and relative humidity. In surveys of the different agro-ecological zones (AEZ) anthracnose was found severe at Ambo (08°58'N, 03r26'E), Meki (08°05'N, 038°51 'E), Arsi-Negele (OrOO'N, 038°35'E), Areka 0 and Bako (09°06'N, 37°09'E), intermediate at Awassa (06°52'N, 038°27'E), Jimma (07°28'N, 035°37'E), and Metu (07°02'N, 35°63'E), and slight to absent at Melkassa (08°23'N', 039°19'E). Other diseases observed included bacterial blight, angular and floury leaf spot and rust. The success rate in breeding for resistance depends to a large extent on the degree of variability in a pathogen. Using the standard differential cultivar set and binomial system proposed by CIAT (Centro Internacional de Agricultutra Tropical), eight races of C. Iindemuthianum, viz. 65, 73 128, 296, 511, 589, 961, and 1027, were identified from Ethiopia and compared to races 3, 6, 81,323,390 and 593 from Southern Africa. Races 128 and 511 constituted more than 50% of all isolates characterised. Considering the differential cultivars, G 2333 was resistant to all races in Ethiopia, and AB 136, G 2333, Kaboon, Cornell 49-242 to all races in Southern Africa. Field studies were conducted at Ambo and Bako (Ethiopia) to evaluate resistant and susceptible cultivar mixtures as a means of anthracnose control. Results showed that disease incidence and severity were consistently lower in mixtures containing 50%, 67% and 80% of the resistant component at both locations. Disease progress curves and disease gradients indicated that disease development and spread were slower or reduced in all treatments that contained an increased proportion of the resistant cultivar. It was thus found that anthracnose could be controlled by growing cultivar mixtures containing at least 60% of a resistant cultivar. In an assessment of the efficacy of chemical control of anthracnose, a benomyl seed dressing followed by a foliar difenoconazole spray, or difenoconazole application alone, showed the most promising results. Finally, greenhouse and multi location field experiments were carried out to identify bean genotypes as possible sources of resistance to Ethiopian isolates of C. lindemuthianum. The study established that cultivars Widusa, GLP X 1132, A 482, A 193, G-7, HAL 5 and G 2333 were valuable sources of anthracnose resistance.

Droëbone (Phaseolus vulgaris L.) is 'n belangrike voedselgewas vir miljoene Ethiopiërs. Siektes speel egter 'n belangrike rol in droëboonproduksie en veral antraknose, veroorsaak deur Colletotrichum lindemuthianum (Sacc. & Magn.) Briosi and Cav. (teleomorf = Glomerella eingulata (Stonem.), verdien spesiale vermelding. Antraknose word beskou as die belangrikste siekte van droëbone in Ethiopië en kan totale oesverliese in vatbare kultivars tot gevolg hê wanneer besmette saad geplant word. Die impak van epidemies word verder vergroot indien gunstige omgewingstoestande voorkom. Die doelwit van hierdie studie was om inligting in te samel wat kan bydra tot 'n antraknose-beheerprogram in Ethiopië. Veldopnames is gedoen in die belangrikste produksie-areas in Ethiopië ten einde .." inligting te bekom oor die geografiese verspreiding van antraknose. Soortgelyk aan roes word antraknose bevoordeel deur hoë vog en relatiewe humiditeit. In opnames van die verskillende agro-ekologiese gebiede is gevind dat antraknose in ernstige graad voorkom by Ambo (08°58'N, 037°26'E), Meki (08°05'N, 038°51 'E), Arsi-Negele (07°00'N, 038°35'E), Areka (06°48'N, 037°43'E) en Bako (09°06'N, 37°09'E), terwyl intermediêre vlakke by Awassa (06°52'N, 038°27'E), Jimma (07°28'N, 035°37'E), en Metu (Or02'N, 35°63'E), en slegs enkele tekens van die siekte by Melkassa (08°23'N', 039°19'E) aangetref is. Ander siektes waargeneem het bakteriese skroei, hoekige blaarvlek, Ramularia-vlek en roes ingesluit. Sukses in weerstandsteling hang tot 'n groot mate af van die hoeveelheid variasie in 'n patogeen. Met behulp van die staandaardstel differensiërende lyne en binomiale nomenklatuursisteem van CIAT (Centro Internaeional de Agrieultutra Tropical), is agt rasse van C. lindemuthianum, nl. 65, 73 128, 296, 511, 589, 961, en 1027, in Ethiopië geïdentifiseer in vergelyking met rasse 3, 6, 81, 323, 390 en 593 in Suidelike Afrika. Rasse 128 en 511 het meer as 50% van alle isolate beslaan. Met in ag neming van die differensieerders was G 2333 bestand teen alle Ethiopiese isolate en AB 136, G 2333, Kaboon en Cornell 49- 242 teen alle isolate uit Suidelike Afrika. Veldproewe is by Ambo en Bako (Ethiopië) uitgevoer om te bepaal tot watter mate kultivarmengsels antraknose kan beheer. Siektevoorkoms en ergheidsgraad was deurgaans laer in mengsels met 50%, 67% en 80% van 'n weerstandbiedende kultivar. Siektevorderingskurwes en siektegradiënte het aangetoon dat ontwikkeling en verspreiding stadiger en meer beperk was in alle behandelings met 'n proporsie bestandheid. Daar is tot die gevolgtrekking gekom dat antraknose beheer kan word in mengsels wat ten minste 60% van 'n bestande kultivar bevat. 'n Beraming van die doeltreffendheid van chemiese antraknose-beheer het aangedui dat In benomyl saadbehandeling, gevolg met 'n difenoconazole loofbespuiting, of laasgenoemde alleen, die beste beheer gegee het. Laastens is glashuis en multilolaliteitsveldproewe gedoen om droëboongenotipes met genetiese weerstand teen Ethiopiese isolate van C. lindemuthianum te identifiseer. Die studie het die kultivars Widusa, GLP X 1132, A 482, A 193, G-7, HAL 5 as G 2333 as waardevolle bronne van antraknose-bestandheid uitgewys.
Thesis (Ph.D. (Plant Sciences (Plant Pathology))--University of the Free State, 2003
Keywords: Common bean -- Diseases and pests -- Control -- Ethiopia; Anthracnose -- Ethiopia